The Lightning Flash - Cooray, Vernon (IET power and energy series, 2014)
This updated and expanded new edition of Cooray's classic text provides the reader with a thorough background in almost every aspect of lightning and its impact on electrical and electronic equipment. The contents range from basic discharge processes in air through transient electromagnetic field generation and interaction with overhead lines and underground cables, to lightning protection and testing techniques. New to this edition are discussions of high-speed video recordings of lightning; rocket-and-wire triggered lightning experiments; tower initiated lightning discharges; upper atmospheric electrical discharges; attachment of lightning flashes to grounded structures; energetic radiation from thunderstorms and lightning; global lightning nitrogen oxides production; and lightning and global temperature change. The Lightning Flash, 2nd Edition is a sound introduction to researchers and advanced students working in the field and of value for anyone designing, installing or commissioning equipment which needs to be secured against lightning strikes.